Inflasi Istilah dalam Kebijakan Pendidikan: Kritik terhadap Produksi Terminologi Baru dalam Kurikulum Indonesia - Hukom, Julham (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This article examines the phenomenon of term inflation in Indonesian curriculum policy, particularly the Independent Curriculum (Kurikulum Merdeka), which is characterized by the widespread production of new terminology without adequate conceptual clarity. The research uses a critical review method based on document analysis and scientific literature to examine how these terms are formulated, adopted, and practiced by stakeholders, particularly teachers. The results show that term inflation often creates ambiguity and a lack of synchronization between policy documents, thus hindering consistent curriculum implementation. Furthermore, teachers face administrative burdens, adaptation pressures, and a tendency to interpret new terms in a formalistic manner due to the lack of stable operational guidelines. This phenomenon not only burdens teachers but also has the potential to undermine the quality of the pedagogical transformation expected from curriculum reform. This article emphasizes that terminology changes must be embedded within a more consistent, coherent, and long-term policy framework so that they do not hinder but instead strengthen educational practices in schools.